Piloting an online incident reporting system in Australasian emergency medicine. (5th August 2014) - Schultz, Timothy J; Crock, Carmel; Hansen, Kim; Deakin, Anita; Gosbell, Andrew
Abstract Background Medical‐specific incident reporting systems are critical to understanding error in healthcare but underreporting by doctors reduces their value. Objective We conducted a pilot study of the implementation of an online ED‐specific incident reporting system in Australasian hospitals and evaluated its use. Methods The reporting system was based on the literature and input of experts. Thirty‐one hospital EDs were approached to pilot the Emergency Medicine Events Register (EMER). The pilot evaluated: website usage and analytics, reporting behaviours and rates, the quality of information collected in EMER. Semi‐structured interviews of three site champions responsible for implementing EMER were conducted. Results Seventeen EDs expressed interest; however, due to delays and other barriers reporting only occurred at three sites. Over 354 days, the website received 362 unique visitors and 77 incidents. The median time to report was 4.6 min. The reporting rate was 0.07 reports per doctor month, suggesting a reporting rate of 0.08% of ED presentations. Data quality, as measured by the number of completed non‐mandatory fields and ability to classify incidents, was very high. The interviews identified enablers (the EMER system, site champions) and barriers (chiefly the context of EM) to EMER uptake. Conclusions Collecting patient safety information by frontline doctors is essential to actively engage the profession in patent safety. Although the EMER system allowed easy online reporting of high quality incident data by doctors, site recruitment and system uptake proved difficult. System use by ED doctors requires dedicated and conscious effort from the profession.